Modeling Metastatic Colonization in a Decellularized Organ Scaffold‐Based Perfusion Bioreactor (Adv. Healthcare Mater. 1/2022). Issue 1 (4th January 2022) - Rafaeva, Maria; Horton, Edward R.; Jensen, Adina R.D.; Madsen, Chris D.; Reuten, Raphael; Willacy, Oliver; Brøchner, Christian B.; Jensen, Thomas H.; Zornhagen, Kamilla Westarp; Crespo, Marina; Grønseth, Dina S.; Nielsen, Sebastian R.; et al.
Abstract : Cancer Metastasis Highlighting article number 2100684 by Janine T. Erler, Alejandro E. Mayorca‐Guiliani and co‐workers, this cover represents cancer cells extravasating out of a vessel into a decellularized extracellular matrix (ECM) organ scaffold. Upon arriving in the capillary bed, the cells adhere to the ECM and use it to migrate into the organ. The authors' metastasis model system is based on a bioreactor where ECM organ scaffolds are provided with the conditions necessary to sustain cell life. Cell‐ECM interactions coerce cells into behaving as they would in a living organism.